Emotion regulation across the lifespan: age differences in intrapersonal and interpersonal strategies for the adjustment to the COVID-19 pandemic in four countries. (3rd October 2022) - Dworakowski, Olenka; Huber, Zilla M.; Meier, Tabea; Boyd, Ryan L.; Horn, Andrea B.
Abstract: Objectives: Studies have shown age differences in adapting to the COVID-19 pandemic. The processes explaining these age differences remain unclear. Intrapersonal and interpersonal emotion regulation play an important role in psycho-social adjustment and develop across the lifespan. This study investigated whether differences in COVID-19-related adjustment disorder symptoms can be explained by age-differences in rumination in a multi-national sample. Furthermore, linguistic indicators of ruminative processing were examined with reference to age. Methods: N = 1401 participants (from USA, UK, Switzerland, Germany, aged 18–88) completed an online survey and a writing task. Measures included brooding, co-brooding, adjustment disorder symptoms, and language indicators of negative self- and communal-focus . Results: Older participants reported less adjustment disorder symptoms which was mediated by less (co-)brooding. Participants reporting more (co-)brooding wrote about COVID-19 more negatively. While in younger adults more self-focus was associated with higher ruminative brooding, in older adults it was associated with less brooding. Conclusion: These findings contribute to a better understanding of regulatory mechanisms that help explain age differences in mental health. They warrant further research considering age-related differences, as our results suggest not only more adaptive emotion regulation as resilience factor in older individuals but also different qualities of self-focus while processing stressful events.